Analysis of the effect of stirrer and container rotation direction on mixing index (Ip) - Susilo, Sugeng Hadi; Asrori, Asrori; Gumono, Gumono (Eastern-European Journal of Enterprise Technologies, 2021)
The paper discusses the effect of the stirrer and container rotation direction on the mixing index (Ip). The chaos theory is the result of an in-depth study of various problems that cannot be answered by the two previous major theories, namely quantum mechanics and the theory of relativity. Effective mixing of the flow area does not depend on rapid stirring. This study uses a container with a double stirrer, camera, programmable logic controller, tachometer, 6 A adapter, and a computer. DC electric motor (25 V) for turning stirrers and housings. The diameter of the primary and secondary stirrers is Dp=38 mm and Ds=17 mm. The diameter of the container made of transparent plastic is Dw=160 mm and height is 170 mm. Primary stirrer rotation (np)=10 rpm, secondary stirrer rotation (ns)=22.3 rpm, and container rotation (nw)=13 rpm, the angular velocity of the container is Ww=360° while the angular speed of the primary stirrer is Wp=180°. The liquid consists of a mixture of water and paint (white). For dye, a mixture of water and paint (red) is used. For testing the Brookfield viscometer, the viscosity of the liquid and dye is used. The results showed that turning the stirrer in the opposite direction to the container, there will be stretching, bending, and folding around the stirrer, and the smallest mixing index was P2V-b (0.94). In addition, based on the mixing index value above, the highest mixing effectiveness level is obtained, namely: P2V-b, P2S-b, P2B-b, P2V-a, P2B-a, and finally P2S-a. The mixing index is inversely related to the effectiveness level. So the highest effectiveness level is given by the following treatment: 1. Variation rotation (between opposite rotating mixers), 2. Opposite rotation (stirrer rotation opposite direction to the container), 3. Unidirectional rotation (stirrer rotation in the direction of the container)